Determinants Affecting Consumer Behaviour With Regard To Counterfeit Products (International Journal of Scientific Research and Management (IJSRM), 2016)
Counterfeiting is the practice of manufacturing, importing/exporting, distributing, selling or otherwise dealing in goods, often of inferior quality, under a trademark that is identical to or substantially indistinguishable from a registered trademark, without the approval or oversight of the registered trademark owner. Counterfeits are most commonly called “fake goods” or “knock-offs.” Many well-known and successful brands, spanning various industries, are victims of counterfeiting. The production and sale of counterfeit goods is a global, multi-billion dollar problem and one that has serious economic and health ramifications for Governments, businesses and consumers